Subterranean Termite Durability of Three Inferior Wood Species Collected from Indonesian New Guinea Coated with Two Coating Systems (Wood Research Journal, 2022)
Wood is very susceptible material from termite attacks. A simple, cheapest method to prevent this attack is coating treatment. On this work, three inferior wood species collected from Manokwari – Papua Barat, namely Pulai (Alstonia scholaris), Binuang (Octomeles sumatrana), and Jambu (Syzygium sp.) were coated with two coating systems of oiled and water- based coatings. Coating was applied using paint brush on wood samples with dimensions, 50 cm long x 5 cm wide x 2.5 cm thick. Durability was conducting with grave yard test, where half-length of wood samples, coated and uncoated samples, were buried on the yard for the three consecutive months. Wood durability was evaluated using two variables, wood weight loss, and wood damage, respectively, and analyses into other variables likes wood resistance class, level of resistance, degree of damage, and natural durability classes. The results indicated that both coated systems, oiled and water based, had an average of spreading rates from 0.005-0.015 g/cm2. Weight loss of three inferior species of wood recorded from the control samples are 38.65%, 12.12%, and 6.14% for Pulai, Binuang and Jambu. Treatment with coating systems, weight loss could be prevented into 95.1%, 58.2% and 56.0% to control for Pulai, Binuang and Jambu, respectively.  Wood resistance class of Pulai is IV. Binuang and jambu species initially is Moderate Resistant (III) and improve into Resistant (II). It is summarized that coating systems available in the local market could protect wood from subterranean termites.